Study of CFRP retrofitted RC column under close-in explosion. (15th January 2021) - Hu, Ye; Chen, Li; Fang, Qin; Kong, Xiangzhen; Shi, Yanchao; Cui, Jian
Highlights: Field tests reveal the influence of different CFRP retrofitting method on the blast performance of RC column. Non-retrofitted end parts are the vulnerable key dominating the residual bearing capacity of damaged column. Increasing the wrapping thickness is the most efficient way to improve the CFRP retrofitting contribution. A formula that can predict the contribution of FRP-retrofitting to blast-resistance of the RC column was proposed. Abstract: To efficiently improve the anti-blast performance of current reinforced concrete (RC) structures, three different retrofitting methods using the carbon fiber reinforced polymer (CFRP) sheets were proposed. Field tests were carried out on the FRP retrofitted columns subjected to close-in and double-end-initiation explosions. The recorded dynamic damage characteristics of RC columns reveal that the proposed methods benefit the lateral resistance and local damage of columns to different extents. A residual bearing capacity experiment was conducted to evaluate different damage levels of the blast damaged column. Brittle failure was observed at both ends of the columns, which were demonstrated to be a vulnerable key to the axial bearing capacity, and where CFRP was inconvenient to wrap. The fine finite element (FE) model of the RC column was established on the LS-DYNA platform, which was validated by both the blast and axial bearing test data. The influences of axial load ratio ( ALR ), longitudinal reinforcement ratio ( ρ g ), CFRP thickness ( H ), charge cylinder aspect ratio ( D/L ), and stirrup ratio ( ρ v ) were studied using the developed model. A new formula to guide retrofitting RC columns based on the residual bearing capacity was proposed, which can quantitatively calculate the retrofitting contribution to the blast resistance of the RC column.